Effects of brain tissue oxygen (PbtO2) guided management on patient outcomes following severe traumatic brain injury: A systematic review and meta-analysis. (May 2022) - Hays, Leanne M.C.; Udy, Andrew; Adamides, Alexios A; Anstey, James R.; Bailey, Michael; Bellapart, Judith; Byrne, Kathleen; Cheng, Andrew; Jamie Cooper, D.; Drummond, Katharine J.; Haenggi, Matthias; Jakob, Stephan M.; et al.
Highlights: Brain tissue oxygen (PbtO2 ) monitoring and optimisation may improve TBI outcomes. We conducted a systematic review/ meta -analysis of RCTs of PbtO2 -guided management. Our findings suggest that PbtO2 -guided management: Increased survival and reduced intracranial pressure. Did not increase respiratory or cardiovascular adverse events. No significant association was identified with improved functional outcomes. The certainty of the available evidence is very low. It is not possible to make any definitive treatment recommendations. Abstract: Monitoring and optimisation of brain tissue oxygen tension (PbtO2 ) has been associated with improved neurological outcome and survival in observational studies of severe traumatic brain injury (TBI). We carried out a systematic review of randomized controlled trials to determine if PbtO2 -guided management is associated with differential neurological outcomes, survival, and adverse events. Searches were carried out to 10 February 2022 in Medline (OvidSP), 11 February in EMBASE (OvidSP) and 8 February in Cochrane library. Randomized controlled trials comparing PbtO2 and ICP-guided management to ICP-guided management alone were included. The primary outcome was survival with favourable neurological outcome at 6-months post injury. Data were extracted by two independent authors and GRADE certainty of evidence assessed. There was no difference in the proportion of patients with favourable neurological outcomes with PbtO2 -guided management (relative risk [RR] 1.42, 95% CI 0.97 to 2.08; p = 0.07; I2 = 0%, very low certainty evidence) but PbtO2 -guided management was associated with reduced mortality (RR 0.54, 95% CI 0.31 to 0.93; p = 0.03; I2 = 42%; very low certainty evidence) and ICP (mean difference (MD) − 4.62, 95% CI − 8.27 to − 0.98; p = 0.01; I2 = 63%; very low certainty evidence). There was no significant difference in the risk of adverse respiratory or cardiovascular events. PbtO2 -guided management in addition to ICP-based care was not significantly associated with increased favourable neurological outcomes, but was associated with increased survival and reduced ICP, with no difference in respiratory or cardiovascular adverse events. However, based on GRADE criteria, the certainty of evidence provided by this meta -analysis was consistently very low. MESH: Brain Ischemia; Intensive Care; Glasgow Outcome Scale; Randomized Controlled Trial; Craniocerebral Trauma.